Peran Penting SERVQUAL Dalam Peningkatan Kepuasan Konsumen di PT Auto Finance Pematangsiantar - Hengki Mangiring Parulian Simarmata; Poltak Pardamean Simarmata; Doris Yolanda Saragih (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2022)
Non-bank financial institutions such as leasing need to provide the best service to consumers. In the midst of high competition between financial institutions and banks, PT Bussan Auto Finance Pematangsiantar must understand the competitive strategy by using a customer service strategy. This study aims to determine the effect of SERVQUAL on consumer satisfaction at PT Auto Finance Pematangsiantar. The sample used in this study was 98 people with a non-probability sampling technique with the slovin model. The primary data collected was then processed using SPSS software. The data were tested with validity, reliability and normality tests. Then a hypothesis test was conducted to determine whether there was a significant effect and a determinant coefficient test was conducted to determine the magnitude of the influence between variables. The results showed that there was a significant positive effect between service quality and customer satisfaction of 76.5% while the remaining 23.5% was influenced by other variables. To develop this research, other variables such as marketing mix and customer relationship management can be used.